(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2001)
Obesity is an element of risk to several pathologies and its prevalence is increasing in many countries. It was considered a serious health problem by the World Health Organization and several kinds of treatment have been proposed to reduce body weight. There is a strong need to systematize the strategies applied in obesity treatment and its results. To this purpose, a Latin-American Obesity Consensus has been elaborated, as a document which describes the efficient and ethical strategies to be applied in such treatments. The aim of this article is describing the applied methodology in the elaboration of this Latin-American Obesity Consensus, its contents and the governamental policies that are being developed to reduce the prevalence of obesity.